The structuring role of free-floating plants on the fish community in a tropical shallow lake: an experimental approach with natural and artificial plants - Teixeira-de Mello, Franco; de Oliveira, Valdeci Antonio; Loverde-Oliveira, Simoni Maria; Huszar, Vera Lucia M.; Barquín, José; Iglesias, Carlos; Silva, Thiago Sanna Freire [UNESP]; Duque-Estrada, Carlos Henrique; Silió-Calzada, Ana; Mazzeo, Néstor (Springer Nature, 2016)
Free-floating plants are important components of aquatic ecosystems in tropical climates, playing a key role in the structure and spatial distribution of fish communities. This study aims at elucidating the potential effects of free-floating vegetation on fish community structure in a tropical floodplain lake, using an experimental approach based on natural and artificial devices (Eichhornia crassipes), in high and low (LT) turbidity waters. A total of 32 fish species were found, richness, abundance, biomass, mean fresh body weight, and standard length were all significantly higher in the LT regions. Although no significant differences of community traits were found between artificial and natural substrates, regardless of water turbidity, fish composition differences between devices were observed in clear waters. Benthivorous fishes were the most widespread trophic group, with higher abundance and biomass in LT, while no differences were found among plant types. The results confirmed the structural role played by free-floating plants in the fish community by offering a refuge to smaller bodied fish species and younger specimens of larger species, independently of turbidity conditions. However, the effect was stronger in clear waters. The evidence also supported the hypothesis that the fish community forages within the plant beds. Turbidity spatial gradients or turbid regimes in tropical shallow lakes, as well as important floating macrophyte coverage could have strong impacts on the fish community structure.
Keywords: Brazil; Food resources; Pantanal; Predation refuge; Trophic interactions; Tropical floodplain